Pengaruh Implementasi Knowledge Sharing terhadap Kinerja Organisasi - Maghfira Sheni Fira; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
Abstract. The implementation of knowledge sharing on the pandemic of Covid-19 is less than the maximum run compared with the normal conditions of time before the occurrence of a pandemic that is caused due to the presence of uncertainty and new habits, so it can be difficult to be able to share knowledge and experience among fellow co-workers. Based on these phenomena, then the problem in this research is formulated as follows: (1) How the implementation of knowledge sharing of employees during the pandemic of Covid-19 in PT. Bank Woori Saudara Indonesia 1906 Tbk KC Surapati Core? (2) How the level of performance of the organization on the pandemic of Covid-19 in PT. Bank Woori Saudara Indonesia 1906 Tbk KC Surapati Core? (3) How big is the influence of the implementation of knowledge sharing on the performance of the organization on the pandemic of Covid-19 in PT Bank Woori Saudara Indonesia 1906 Tbk KC Surapati Core?. The research method used is survey method, because the instrument in this study used a questionnaire and an interview. The data analysis technique used in this research is descriptive analysis techniques and verification with quantitative approach. Collection of data obtained through interviews, questionnaires, literature study and documentation. The sample in this research is employees of PT. Bank Woori Saudara Indonesia 1906 Tbk KC Surapati Core, which amounted to 32 people. The results of this Study are: There is a positive influence and significantly, the implementation of knowledge sharing partially on the performance of the organization on the pandemic of Covid-19 in PT. Bank Woori Saudara Indonesia KC Surapati Core. Abstrak. Implementasi knowledge sharing pada masa pandemi Covid-19 kurang maksimal dijalankan dibandingkan dengan kondisi normal saat sebelum terjadinya pandemi yang disebabkan karena adanya ketidakpastian dan kebiasaan baru, sehingga dapat menyulitkan untuk bisa berbagi pengetahuan dan pengalaman yang dimiliki antar sesama rekan kerja. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana implementasi knowledge sharing karyawan pada masa pandemi Covid-19 di PT. Bank Woori Saudara Indonesia 1906, Tbk KC Surapati Core? (2) Bagaimana tingkat kinerja organisasi pada masa pandemi Covid-19 di PT. Bank Woori Saudara Indonesia 1906, Tbk KC Surapati Core? (3) Seberapa besar pengaruh implementasi knowledge sharing terhadap kinerja organisasi pada masa pandemi Covid-19 di PT Bank Woori Saudara Indonesia 1906, Tbk KC Surapati Core?. Metode penelitian yang digunakan adalah metode survei, karena instrumen dalam penelitian ini menggunakan kuesioner dan wawancara. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis deskriptif dan verifikatif dengan pendekatan kuantitatif. Pengumpulan data yang diperoleh melalui wawancara, kuesioner, studi kepustakaan dan dokumentasi. Sampel dalam penelitian ini adalah karyawan PT. Bank Woori Saudara Indonesia 1906, Tbk KC Surapati Core yang berjumlah 32 orang. Hasil Penelitian ini adalah: Terdapat pengaruh positif dan signifkan implementasi knowledge sharing secara parsial terhadap kinerja organisasi pada masa pandemi Covid-19 di PT. Bank Woori Saudara Indonesia KC Surapati Core.